Molecular cloning of genes encoding branched-chain keto acid dehydrogenase of Pseudomonas putida. - Sykes, P J (1987)
We cloned the structural genes for the individual subunits of the branched-chain keto acid dehydrogenase multienzyme complex on a 7.8-kilobase EcoRI-SstI restriction fragment of Pseudomonas putida chromosomal DNA by cloning into the broad-host-range vector pKT230. A direct selection system for growth on valine-isoleucine agar was achieved by complementation of P. putida branched-chain keto acid dehydrogenase mutants. The recombinant plasmid, pSS1-1, increased expression of branched-chain keto acid dehydrogenase up to five times in wild-type P. putida. The complex was expressed constitutively in P. putida(pSS1-1) but was inducible in Escherichia coli HB101(pSS1-1) by high valine. E. coli minicells transformed with pSS1-1 produced three polypeptides which did not match the four polypeptides of the purified complex. To resolve this problem, we inserted P. putida DNA from pSS1-1 into pUC18 and pUC19. The pUC-derived plasmids were used as DNA templates in an E. coli transcription-translation system. Four polypeptides were produced from the pUC18-derived plasmid which had the correct molecular weights, showing that the structural genes had been cloned. Since only weak bands were produced with the pUC19-derived plasmid, the direction of transcription was established. The locations and order of all the structural genes of branched-chain keto acid dehydrogenase were located by restriction enzyme mapping.